Students’ Strategies in Solving PISA Mathematical Problems Reviewed from Problem-Solving Strategies - Meryansumayeka Meryansumayeka; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Cecil Hiltrimartin (Universitas Sriwijaya, 2021)
This study purposes to describe the strategies used by students in solving PISA type problems seen from the strategy of problem solving according to Polya. The research methodology is qualitative type descriptive study. Research subjects were 6 high school students in Palembang who had different levels of mathematical ability. Data was gathered using observation, interviews, and student answer sheets on the type of PISA questions given. The results showed that the dominant strategy used by students in solving PISA type problems included making pictures when they solve problem related to geometry; looking for possible answers systematically when they try to solve problem within numeric; writing information stated and the question when the problem is in the form of storytelling; and using trial and error when the problem provide answer alternatives.